2012
DOI: 10.1007/s12282-012-0427-1
|View full text |Cite
|
Sign up to set email alerts
|

Procedures for location of non-palpable breast lesions: a systematic review for the radiologist

Abstract: Accurate location of small breast lesions is mandatory for proper surgical management. The purpose of this article is systematically review procedures used to locate non-palpable breast lesions, including a description of the current status, advantages, and disadvantages for each technique. A total of 47 articles were finally included: 7 articles for the wire location technique, 5 articles for the radioguided location technique, 13 articles that compare wire location with radioguided location, 3 articles for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…The detection of impalpable breast lesions by mammography has become more common, accounting for ~25% of diagnosed breast pathologies (1). The detection of impalpable breast lesions generates questions associated with the nature of the lesion (benign or malignant) and, consequently, with the conduct of the investigation to be executed.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of impalpable breast lesions by mammography has become more common, accounting for ~25% of diagnosed breast pathologies (1). The detection of impalpable breast lesions generates questions associated with the nature of the lesion (benign or malignant) and, consequently, with the conduct of the investigation to be executed.…”
Section: Introductionmentioning
confidence: 99%
“…Dislodging and poor localization are causes for relatively high irradicality rates for WGL ranging from 10% to 50% [4,8,[16][17][18][19][20][21][22][23]. Radioguided occult lesion localization (ROLL) was developed in 1996, and is nowadays used in several institutes as a reliable alternative for WGL [5,20,[24][25][26][27][28][29]. The principle of this technique consists of an image (frequently ultrasound and stereotaxis) guided intratumoral injection of a radioactive tracer (most commonly used is Technetium-99m ( 99m Tc) macro-aggregate albumin), which is retained within the tumor and can be detected by the surgeon using a gamma probe.…”
Section: Introductionmentioning
confidence: 99%
“…It was anticipated that a GSSE short course would improve participants' success in passing the GSSE, although there are few published studies on the success of courses with similar objectives. [1][2][3][4][5]…”
Section: The Generic Surgical Sciences Examination Training Programmementioning
confidence: 99%
“…For an overview of LLTs, the reader is referred to the following articles. 3,4 Optimal BCS aims for negative margins with minimal removal of normal tissue, both of which are influenced by LLT. Studies have reported poor lesion centring within the excised tissue, with involvement of margins, and excessive tissue removal at others.…”
mentioning
confidence: 99%